Spectacles of death in ancient Rome - Kyle, Donald G. (Routledge, 1998)
The elaborate and inventive slaughter of humans and animals in the arena fed an insatiable desire for violent spectacle among the Roman people. Donald G. Kyle combines the words of ancient authors with current scholarly research and cross-cultural perspectives, as he explores* the origins and historical development of the games* who the victims were and why they were chosen* how the Romans disposed of the thousands of resulting corpses* the complex religious and ritual aspects of institutionalised violence* the particularly savage treatment given to defiant Christians. T.